2020
DOI: 10.3390/cells9112354
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia Advocates Functional Mitochondria and Alleviates Oxidative Stress to Combat Acetaminophen-Induced Hepatotoxicity

Abstract: For years, moderate hypothermia (32 °C) has been proposed as an unorthodox therapy for liver injuries, with proven hepatoprotective potential. Yet, limited mechanistic understanding has largely denied its acceptance over conventional pharmaceuticals for hepatoprotection. Today, facing a high prevalence of acetaminophen-induced liver injury (AILI) which accounts for the highest incidence of acute liver failure, hypothermia was evaluated as a potential therapy to combat AILI. For which, transforming growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…From our past study, moderate hypothermia was shown to render concomitant mitophagy and mitochondrial biogenesis vitro 2 . We thus inquired on their existence in a pulsed cooling animal model, to abate mitochondrial dysfunction in AILI.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…From our past study, moderate hypothermia was shown to render concomitant mitophagy and mitochondrial biogenesis vitro 2 . We thus inquired on their existence in a pulsed cooling animal model, to abate mitochondrial dysfunction in AILI.…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies have characterized the effects of hypothermia on AILI in vitro 1 , 2 . With this established understanding, we hoped to translate the concept of hypothermic treatment into a clinically actionable therapy-one which achieved hepatoprotection with minimal invasiveness and adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations